2016
DOI: 10.1002/chin.201622215
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Chemical Constituents from the Fermented Mycelia of the Medicinal Fungus Xylaria nigripes.

Abstract: Compounds (I), (II), and (III) are isolated from the ethanol extract of the fermented mycelia of Xylaria nigripes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…An absorption band at 291 nm in the UV spectrum of compound 1 was indicative of a pyrrole-2-aldehyde moiety [ 14 ]. The 1 H-NMR spectrum ( Table 1 , supplementary material Figure S1 ) displayed a set of two mutual coupled protons at δ H 6.98 (1H, d, J = 4.2 Hz, H-3) and 6.23 (1H, d, J = 4.2 Hz, H-4), which indicated the presence of a typical 2,5-disubstituted pyrrole ring [ 15 , 16 ]. The presence of an aldehyde group in compound 1 was supported by the NMR signals at δ H 9.44 (1H, s) and δ C 179.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An absorption band at 291 nm in the UV spectrum of compound 1 was indicative of a pyrrole-2-aldehyde moiety [ 14 ]. The 1 H-NMR spectrum ( Table 1 , supplementary material Figure S1 ) displayed a set of two mutual coupled protons at δ H 6.98 (1H, d, J = 4.2 Hz, H-3) and 6.23 (1H, d, J = 4.2 Hz, H-4), which indicated the presence of a typical 2,5-disubstituted pyrrole ring [ 15 , 16 ]. The presence of an aldehyde group in compound 1 was supported by the NMR signals at δ H 9.44 (1H, s) and δ C 179.5.…”
Section: Resultsmentioning
confidence: 99%
“…Until now, nearly 200 naturally occurring alkaloids with a pyrrole-2-aldehyde moiety have been reported. These kind of alkaloids are widely distributed in plants, microorganisms, and marine invertebrates [ 16 , 17 , 18 , 19 ]. However, compounds 1 – 7 with the pyrrole-2-aldehyde group were first isolated from the edible mushroom Phlebopus portentosus .…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 , 8 , 10 Recently, bioactive compounds with neuroprotective, anti-neuroinflammatory, and cytotoxic properties were isolated from XN mycelia. 11 However, no study has reported detailed mechanisms regarding the neuroprotection of XN mycelia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, bioactive compounds with neuroprotective, anti-neuroinflammatory, and cytotoxic properties were isolated from XN mycelia. 11 However, no study has reported detailed mechanisms regarding the neuroprotection of XN mycelia. This study demonstrates the neuroprotective effect of XN mycelia extracts on H 2 O 2 -induced cytotoxicity in PC12 cells through multiple mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation